Efeitos da invasão de espécies de Cichla nos padrões taxonômicos e funcionais da assembleia de peixes da planície de inundação do alto rio Paraná. - Rauber, Rafaela Giacomel (2022)
Invasive species cause loss of diversity in introduced sites. Species of the genus Cichla, popular tucunaré or peacock bass, are known for their voracious behavior that makes them a target in sport fishing and a predator with great negative impacts on introduced sites. There is a visible controversy around the species, since the scientific literature points out more and more impacts and the legislation seek ways to increase introductions, generating propagule pressure and prohibiting fishing in invaded places. In addition, mostpapers are punctual and in anthropized places such as reservoirs. Thus, we investigated how the abundance of Cichla individuals affects the assemblage of a floodplain over a time series. We investigated the effects of Cichla on taxonomic attributes of the assemblage (richness, evenness, diversity, abundance, and body length) and on species composition (beta diversity). In addition, the effects of Cichla on functional indices of the assemblage (functional richness, functional equitability, functional divergence, and functional dispersion) are investigated. Cichlaimpacts were evident in changes in beta and functional diversities. Cichla helped in the fauna homogenization process, increasing nestedness and reducing turnover. Additionally, it increased species with similar and more common traits and reduced species with rare traits, reducing dispersion, evenness, richness and functional divergence, it is worth noting that some results appeared with a delay, that is, some impacts make some time to appear in the invaded assembly.Our results showed that Cichlaspecies are capable of changing diversity patterns even in natural environments with great diversity of habitats and species, causing ecological losses that can lead to large economic and ecosystem losses.